Altuvoct: Innovative Medicinal Products Benefit from Innovative Approaches to Regulatory Assessment - Essam Kerwash; Maria Malamatari; John D. Johnston (Life)
Efanesoctocog alfa (Altuvoct; BIVV001) is a fusion protein comprising domains of (i) factor VIII, (ii) the von Willebrand factor, and (iii) IgG1 coupled to two polypeptide linkers. The half-life of efanesoctocog alfa in plasma is about 40 h. The polypeptide linkers are released by thrombin activation, resulting in an active form of efanesoctocog alfa that results in the formation of a fibrin clot. Data from two single-arm ongoing studies were submitted: the XTEND-1 study enrolled 159 subjects aged 12–72 years, and the XTEND-kids study enrolled 74 subjects aged <12 years; all subjects had severe haemophilia A. Single-arm studies are not amenable to conventional statistical analysis of ‘effect of cause’, and so a supplementary analysis was conducted on the basis of ‘cause of effect’, making use of the scheme described by Toulmin coupled to an analysis of causal inference. Overall, the claim that Altuvoct is indicated to treat people aged ≥2 years with severe (and moderate) haemophilia A was considered to be supported by the results of the submitted studies and associated modelling exercises; the benefit–risk evaluation of Altuvoct was found to be positive in the target population.